Incidencia y daño de insectos en la techumbre de madera de cinco edificios históricos (templos) de Michoacán - Jurado Vargas, César Marco Aurelio (Universidad Michoacana de San Nicolas de Hidalgo, 2020)
The incidence and damage caused by xylophagous insects was evaluated in two annual cycles of (April 2017 to March 2018), with the capture of adults by means of the light trap, 53,511 insects associated with wooden roofing were obtained in five Michoacán temples. The analysis of results recognized in the temple of Taretan, the greatest incidence and deterioration caused by xylophage’s species, the main pest is the dry wood termite C. brevis (Kalotermitidae), in addition to Incisitermes sp. n. The Rhinotermitidae family a: C. testaceus, Heterotermes sp n. The Ptinidae family with S. paniceum, four new species: P. escotus sp. n., Petalium sp. 2, C. semioblongus sp. n., C. robustus sp. n. In the temple of Nuevo Urecho the main plague was (Kalotermitidae) C. brevis, in addition to Marginitermes sp. n., of Rhinotermitidae: Heterotermes. sp. n., C. testaceus. From Ptinidae to S. paniceum, L. serricornis, and Petalium sp. n.2, of minor importance. In the temperate region in the temples of Ucareo, Tacicuaro and Ario de Rosales, (Ptinidae) C. oblongus was the most important, associated with dry wood termites, in Tacícuaro: P. tacicuarensis sp. n., in Ario de Rosales: I. marginipennis and in Ucareo only the presence of one specimen of this species was detected, with no evidence of damage to the roof.

Se evaluó la incidencia y daño causado por insectos xilófagos en dos ciclos anuales de (abril de 2017 a marzo de 2018), con la captura de adultos por medio de la trampa de luz, se obtuvieron 53,511 insectos asociados a la techumbre de madera en cinco templos de Michoacán. El análisis de resultados reconocen en el templo de Taretan, la mayor incidencia y deterioro causado por especies xilófagas, la principal plaga es la termita de madera seca C. brevis (Kalotermitidae), además de Incisitermes sp. n. La familia Rhinotermitidae: C. testaceus, Heterotermes sp n. La familia Ptinidae: S. paniceum, cuatro nuevas especies: P. escotus sp. n., Petalium sp. 2, C. semioblongus sp. n., C. robustus sp. n. En el templo de Nuevo Urecho la principal plaga fue (Kalotermitidae) C. brevis, además de Marginitermes sp. n., de Rhinotermitidae: Heterotermes. sp. n., C. testaceus. De Ptinidae a S. paniceum, L. serricornis, y Petalium sp. n.2, de menor importancia. En la región templada los templos de Ucareo, Tacicuaro y Ario de Rosales, (Ptinidae) C. oblongus fue la más importante, asociada con termitas de madera seca. Tacicuaro: P. tacicuarensis sp. n., Ario de Rosales: I. marginipennis y en Ucareo solo se detectó la presencia de un ejemplar de esta especie, sin evidencia de daño en la techumbre.
Facultad de Ingeniería en Tecnología de la Madera. Doctorado en Ciencias y Tecnología de la Madera
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2687; info:eu-repo/classification/cti/7; FITECMA-R-D-2020-1091; Xilófagos; Techumbre; Iglesias